Violência doméstica e implicações socioeconômicas: um estudo sobre enlaces, negociações e rupturas - Oliveira, Francelma Lima Ramos De (2021)
This research was proposed from the need to identify the economic implications and to what extent they influence the causes of violence against women in Itacoatiara, and thus contribute to the SAMIC/CASA DE MARIA project to strengthen and help more victims of violence who seek him. The social contribution will be to strengthen the project, in every way, but especially with regard to encouraging these women to return to the labor market and thus be able to get out of the cycle of violence in which they live. The general objective was: To analyze the economic and financial implications in cases of domestic violence against women assisted by the SAMIC/Casa de Maria project in Itacoatiara in the State of Amazonas. As specific objectives: to describe the economic-financial profile of the victims participating in the research who made the spontaneous denunciation of their aggressors; identify through the narrative of women victims the effects of economic and financial dependence in cases of Domestic Violence; propose guidelines for a protection network focused on the economic and financial situation of victims of violence against women or subsidies for strengthening the protection network of these women. The vision proposed in the light of Pierre Bourdieu theory and its main concepts was adopted: habitus, field and capital, where we will also address the concept of symbolic violence presented in his work, Male Domination. The research took a qualitative approach, with documental analysis and field research. The research included 09 victims of violence against women assisted by the SAMIC/Casa de Maria project, who agreed to participate in the research. Semi-structured interviews were carried out for data collection. Subsequently, the theoretical and technical foundations of the authors Bardin and Minayo were used, going through three phases: exploratory, data collection and analysis of collected data. The data are articulated in three chapters, according to the specific objectives of the research. In the first chapter, the sociodemographic and economic-financial profile of the victims was drawn. In the second chapter, the narratives of the women in the project, the place of violence and its relationship with economic and financial aspects are analyzed, as well as the habitus of the housewife and male domination, marriage as a field and finally patriarchy as dominant culture and its effects on women's lives and the third chapter presents symbolic violence and the emotions of women who denounced men who were perpetrators of violence. Thus, it is important to consider that the guidelines for the protection network focused on the economic and financial situation of victims of violence against women in Itacoatiara is a very important alternative for the project to strengthen and help reduce violence against women in the municipality. The results obtained can be considered satisfactory for the research, as these victims, included in the project, demonstrate through their narratives that they know they have rights and that they are victims of a crime, but fear added to economic and financial dependence makes them postpone going to the police station to report their aggressors.